PSYCHOLOGICAL CONFLICTS EXPERIENCED BY THE CHARACTERS IN THE NOVEL "THE LONELIEST GIRL IN THE UNIVERSE" - Djamal, Auliya Amaliyah; Nur, Sahril (ELITERATE : Journal of English Linguistics and Literature Studies, 2023)
This study discussed the psychological conflict experienced by the main character in the novel “The Loneliest Girl in the Universe” by Lauren James. In this study, the researchers examine the forms and the factors of psychological conflict of the main character in the novel, namely Romy Silvers and J Shoreditch. In researching the forms of psychological conflict, the researchers use the theory of Kurt Lewin (1935) and for the factors; the researchers use the theory of needs by Abraham Maslow (1943). Descriptive qualitative methods were used in this research, in which the researchers read the novel, observed, and analyzed the data. The researchers found that the main character experiences psychological conflict with the types of approach-approach conflict, approach-avoidance conflict, avoidance-avoidance conflict, and multiple approach-avoidance conflicts. Besides that, most of the psychological conflicts experienced by the two main characters in this novel are caused by basic needs.